Convergence of gender roles in a globalized world: international comparison of family and gender roles - García-Faroldi, Livia (My University, 2016)
This paper examines emerging and changing gender roles in different regions of the world. Using data on 12 countries from last three ISSP Special Modules “Family and Changing Gender Roles” (1994, 2002 and 2012), we compare the evolution of gender roles about motherhood and fatherhood and its relation with the extension of women as breadwinners around the world: four Western Europe countries, representatives of different models of Welfare State (Germany, United Kingdom, Norway and Spain) plus United States, three former Soviet nations (Russia, Poland and Czech Republic), two Latin American countries (Chile and Mexico) and two Asian nations (Japan and Taiwan). Data show that family change (measured both in terms of attitudes and social practices) is spreading from Western contexts to other regions of the world, although the pace of this change varies from one country to another, depending on cultural, economic and political factors.
Keywords: Identidad sexual; Gender; Globalization; Family